The anomalously thundery month of June 1925 in southwest Spain: description and synoptic analysis - F. J. Acero; M. Antón; A. J. P. Aparicio; A. J. P. Aparicio; N. Bravo-Paredes; V. M. S. Carrasco; M. C. Gallego; J. A. García; M. Núñez; I. Tovar; J. Vaquero-Martínez; J. M. Vaquero (Natural Hazards and Earth System Sciences)
In a routine search for meteorological events with a great impact on society in the Extremadura region (southwest interior of the Iberian Peninsula) using newspapers, the month of June 1925 was detected as exceptional due to the large number of thunderstorms associated with significant losses of human lives and material resources. This extraordinary month underwent a detailed examination from various complementary perspectives. Firstly, we reconstructed the history of the events, considering the most impacted locations and the resulting damage. Periodical publications, especially the widely circulated Extremadura newspaper in 1925, were pivotal in this regard. Secondly, we scrutinized monthly meteorological variables (precipitation, temperature, and cloudiness) using the lengthiest-available data series from the Iberian Peninsula. This aimed to underscore the exceptional characteristics of June 1925. Lastly, we analyzed the synoptic situation of the thunderstorm events by employing National Oceanic and Atmospheric Administration/Cooperative Institute for Research in Environmental Sciences/Department of Energy (NOAA/CIRES/DOE) 20th Century Reanalysis V3 (20CR) data. This approach allowed us to comprehend, from a synoptic perspective, the exceptional nature of this month. Thereby, a combination of a negative North Atlantic Oscillation (NAO) situation, elevated convective available potential energy (CAPE) values, large-scale lifting, and abundant precipitable water availability in the region was revealed.